Moreover: Reading Alfred Starr Hamilton. Issue 1 (April 2021) - Wilkinson, John
Abstract : This article addresses the challenge to professionalised practices of reading represented by the oeuvre of Alfred Starr Hamilton (1914–2005), with broader implications for the contested category of Outsider Writing. Drawing on the author's experience, three types of early life encounter with poetry are specified, guided to its objects by cultural and parental authority and later reaction against them: a fetish of the book and representations of the poet, oral pleasure, and the magic of the word as an illimitably productive and plastic material. These are linked to encounter with Hamilton's poetry, at once unrelentingly repetitive, and sponsored and structured by a small seedbank of magic words, occasioning the sudden florescence of beauty. To read Hamilton requires a feline practice of submitting to reverie while registering disturbance and aesthetic shock precisely.